Literatura e cinema: a imagem da mulher, segundo Victor Hugo e Tom Hooper, em Os miseráveis - Costa, Anne Carine Lemos Cardoso (2023)
Les Misérables (1862) is a social novel written by Victor Hugo that addressed the social ills of France in the 19th century. In 2012, this literary work won a musical film adaptation in English, directed by Tom Hooper, in contemporary molds. This research addresses the feminine in Victor Hugo's Les Misérables and in its 2012 adaptation, due to the fact that women are catalytic elements of actions in both narratives and are just as active as the male characters commonly analyzed in several studies of different areas. Thus, the main objective of this study is to investigate the construction of the feminine in the prominent characters of the film, mainly in relation to the image and role of women. Considering the attributions determined by the patriarchy in force at that time and even today, we seek to analyze how these women are represented, with the support of theories of feminism, literature and adaptation. Therefore, this research is based on studies by Hutcheon (2013), Stam (2006) and Cunha (2018), in the field of cinema; Llosa (2012), Barthes (2004) and Eagleton (2017), in the literary field; Beauvoir (2009), Lerner (2019), and Davis (2016), in the field of feminism, among other scholars. In this way, this study intends to contribute to future research in order to emphasize the importance of always being aware of the different roles that women can play in society and demystify mistakenly conceived stereotypes throughout history